Medicines for the management of overweight and obesity: A systematic review with network meta-analysis - Gabriela Masiero Marcon; Jhonatan Mendes Paiva; Mariana Delariva Sakiyama; Fernanda Stumpf Tonin; Fernando Fernandez-Llimos; Suzane Virtuoso; Andreia Cristina Conegero Sanches (Brazilian Journal of Pharmaceutical Sciences)
Abstract To synthesize the evidence about pharmacologic treatment of obesity and overweight and to define the options with the best risk-benefit using the stochastic analysis of multicriteria acceptability (SMAA). The analysis addresses a systematic review (PROSPERO CRD42023423308) whose research was realized in PubMed, Scopus, and Web of Science. Randomized controlled trials were included, which verified the effects of sibutramine, orlistat, liraglutide, and semaglutide in patients with IMC ≥ 26 Kg/ m². The risk of bias analysis was performed with RoB 2.0 and the outcomes evaluated were weight loss and serious adverse events. A total of 102 studies with 45.047 participants were included. The network meta-analysis revealed that all the treatments were significantly more effective than the placebo in weight reduction. The use of semaglutide (especially 0.4 mg/day) was associated with a bigger weight loss in comparison to all the other treatments (p<0.05) and the analysis of SMAA showed a risk-benefit of 95%. Besides that, we suggest re-evaluating of sibutramine 10mg/day as a therapeutic option for patients without hypertension or cardiovascular diseases, and we demonstrate the modest weight loss promoted by orlistat 120mg, sibutramine 5mg, and liraglutide 1,8mg and advise against its use, once the benefits do not outweigh the risks.